OP91 Does Anonymity Increase the Reporting of Mental Health Symptoms?. (17th September 2012) - Fear, NT; Seddon, R; Jones, N; Greenberg, N; Wessely, S
Abstract : Background: There is no doubt that the perceived stigma of having a mental disorder acts as a barrier to help seeking. It is possible that individuals may be reluctant to admit to symptoms suggestive of poor mental health when data can be linked to them, even if their personal details are only used to help them access care. This may be particularly relevant because individuals who have a mental health problem are more likely to experience barriers to care and hold stigmatising beliefs. If that is the case, then mental health screening programmes where personal details are required may not be effective in detecting those most in need of care. We aimed to compare mental health symptom reporting when using an anonymous versus identifiable questionnaire among UK military personnel on deployment in Iraq (early 2009). Methods: This was a survey among UK military personnel using two questionnaires, one anonymous (n=315) and one identifiable (n=296). Questionnaires were distributed by alternative allocation. The questionnaire included the 12-item General Health Questionnaire (measuring symptoms of common mental disorder, CMD), the Post-Traumatic Stress Disorder (PTSD) Checklist Civilian Version (measuring probable PTSD) and 11 stigma statements relating to barriers of care and perceived social stigma. Results: Of 612 personnel approached to take part, 99.8% completed the survey. The overall prevalence of probable PTSD was 3.3% and 20.5% for symptoms of CMD. No significant difference in the reporting of symptoms of CMD was found (18.1% identifiable vs. 22.9% anonymous, P=0.150). Personnel were more likely to report borderline and probable PTSD when completing questionnaires anonymously (borderline PTSD: 2.4% identifiable vs. 5.8% anonymous; probable PTSD: 1.7% identifiable vs. 4.8% anonymous, P=0.022). Of the 11 barriers to care and perceived social stigma statements considered, those completing the anonymous questionnaire were more likely to endorse: "leaders discourage the use of mental health services" (9.3% vs. 4.6%, P=0.029), "it would be too embarrassing" (41.6% vs. 32.5%, P=0.023) and "I would be seen as weak" (46.6% vs. 34.2%, P=0.003). Conclusion: We found a significant effect on the reporting of PTSD and certain stigmatising beliefs (but not CMD) when using an anonymous compared to identifiable questionnaire. Our findings have implications for the current post-deployment screening policy used in the US militaryin which identifiable data are collected. These results suggest that researchers need to weigh up the balance between full anonymisation against the use of non-anonymised but confidential survey methods, which permit future follow up.